707 Principles of Damage Control Surgery in Trauma and Beyond: Experience at A Tertiary Centre. (12th October 2021) - Quake, S Y L; Strong, C; Okpala, A; Shaaban, M
Abstract: Damage control surgery (DCS) is an abbreviated laparotomy used as a temporising measure in critically unwell patients who have limited physiological reserves to tolerate complex definitive surgeries. The aim of DCS is to address life-threatening haemorrhage and manage abdominal contamination. Following an abbreviated laparotomy, patients are continuously resuscitated in intensive care unit until physiological stability can be maintained for definitive surgeries. The role of DCS in the trauma setting is well-described; however, its principles can also be applied in General Surgery for a variety of indications such as mesenteric ischaemia, uncontrolled haemorrhage, and secondary peritonitis. Judicious selection of the non-trauma patient who will benefit from this strategy is paramount. We present two cases of a polytrauma patient (Patient A), and non-trauma patient with abdominal septic shock (Patient B) who underwent DCS at our tertiary centre. Patient A is a 49-year-old male involved in a road traffic accident who sustained multiple injuries including liver laceration, splenic laceration, and colonic injury. Intra-abdominal packing and repair of serosal tears were performed, with a re-look laparotomy 48 hours later -- no further bleeding or visceral injuries were identified. Patient B is a 51-year-old gentleman who re-presented in septic shock due to infected retroperitoneal collection following a bleeding duodenal ulcer, initially managed radiologically. A T tube was inserted into the duodenum with two abdominal drains at initial DCS. After thorough washout, a feeding jejunostomy was sited at the re-look laparotomy. 30-days mortality is 0% and both patients are under follow-up.